Identidad cultural y desarrollo del turismo comunitario en la parroquia Jambelí del cantón Santa Rosa - Mendoza Caamaño, Alex Efren (2018)
The present work has as objective to determine the causes that generate the deficit of strategies of promotion of community tourism for the preservation of the cultural identity oriented to a local community development. The Jambelí parish consists of five rural islands, which have a natural diversity, as well as an immeasurable cultural wealth and beautiful landscapes, which would serve as tourist spaces for visitors, while strengthening local economic development, for the inhabitants of each of the islands. The island of Costa Rica is the parish capital of Jambelí, along with Pongalillo, Casitas, Bellavista and San Gregorio are considered for their natural, cultural and archaeological attractions, a great example of this is the sighting of cetaceans. However, the deficit of strategies and the limited use of resources as a cultural identity that the zones have throughout their history; being untapped the wealth both tangible and intangible, consequently focuses on knowing the historical-cultural identity of each of the islands and how you can take advantage of this knowledge for an adequate tourist dissemination in the island communities. The information obtained from the inhabitants of the Jambelí parish was related to cultural aspects, social interactions, outstanding stories, community development, community organization, etc., in order to propose an intervention project that allows improving the quality of life of the population. The focus of this research was qualitative, since the information was gathered based on facts, historical and cultural data, that happened in the parish; The parameters were taken into consideration for the interview were groups of older adults especially people who continue to live since the founding of the parish, in the same way to people who have extensive historical - cultural knowledge and have made it very useful in this studio. According to the results of the empirical research, it was addressed in aspects such as: the reasons for settlement in the islands, the customs and ancestral traditions of the parish, the historical facts a fact in particular the Peruvian invasion in 1941, the legends As part of its cultural identity, the main ancestral economic activities up to its present, the organizations or companies that support economic development and how the inhabitants are organized in the promotion of community tourism. The investigation carried out was conclusive that the loss of cultural identity of the parish is due to the inexistence of historical documentation that reflects their customs and traditions obtaining a sense of belonging; in turn, the deficit of strengthening in the creation of a community tourism center being the main cause the lack of organization among the inhabitants. For this reason, in the third chapter of the research, the Logical Framework planning matrix is proposed as a proposal, which exposes three concrete results such as: strengthening of organizations dedicated to community tourism, organizations with knowledge in sustainable development and environmental preservation, and a management model between tourism organizations - GAD and community; In view of the aforementioned, the proposal was made with technical, methodological and operational requirements for its validation.